Injury prevention in women's gymnastics - Sands, W. A. (Sports Medicine, 2000)
The most serious problem faced by contemporary gymnasts is injury. Given that prevention is superior to treatment, can the gymnastics community and the scientific and medical community do a better job at injury prevention? Most research in gymnastics has been descriptive in nature. Injury prevention ultimately requires that one can predict the outcome of certain activities and their injurious nature. Making such predictions requires a knowledge of the scientific and medical aspects of injury, but more than that, one must have an intimate knowledge of the sport. Injury prevention efforts must be firmly grounded in science and medicine while making pragmatic linkages to gymnastics as it exists and is practiced. This article attempts to bridge the gap between the scientific and medical community and what actually happens in gymnastics.